2024
DOI: 10.1007/s11259-024-10317-z
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence study of brucellosis in wild boar hunted for private consumption in northeast Portugal

Zita Martins Ruano,
Teresa Letra Mateus,
Ana Chorense
et al.

Abstract: Brucellosis is an important infectious disease caused by bacteria of the genus Brucella. In the northeast region of Portugal, infection with Brucella melitensis is endemic in small ruminants, and there are also humans’ cases. However, the epidemiological role of the wild boar in the dynamics of this disease in this region is unknown. In this study, a total of 332 blood samples were collected from wild boar hunted in thirty-six hunting areas during the 2022/2023 hunting season. All were taken by the hunters for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…has also been detected in the Portuguese human population [ 46 , 47 , 48 , 49 ]. A previous study carried out in 332 wild boars reported an apparent seroprevalence of 26.5% in the North region of Portugal [ 32 ]. Several studies have been conducted in Europe to investigate the prevalence of Brucella infections in wild boar populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…has also been detected in the Portuguese human population [ 46 , 47 , 48 , 49 ]. A previous study carried out in 332 wild boars reported an apparent seroprevalence of 26.5% in the North region of Portugal [ 32 ]. Several studies have been conducted in Europe to investigate the prevalence of Brucella infections in wild boar populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although related infections have been discovered in numerous places throughout the world, there have only been a few seroepidemiological studies on Brucella spp. in wild ungulates in Portugal [ 32 , 33 ]. The epidemiological state of wild animals in Portugal, such as red deer, is virtually unknown.…”
Section: Introductionmentioning
confidence: 99%